LITERATURE REVIEW FACTORS AFFECTING DECISION MAKING AND CAREER PLANNING: ENVIRONMENT, EXPERIENCE AND SKILL - Pascariati, Prima Sari; Ali, Hapzi (Dinasti International Journal of Digital Business Management, 2022)
The development of a research role from previous or relevant research is significant because it can help strengthen theoretical studies and the phenomenon of the relationship or influence between variables in a study. This article reviews and seeks to confirm the factors that influence decision-making and career planning, including environment, experience, and skills. This article aims to build a hypothesis of the influence between variables to be used in further research. Human Resource Management literature study results from library research are that: 1) Environment influences decision making; 2) Experience influences decision making; 3) Skills influence decision making; 4) decision making affects career planning; 5) Environment influences career planning; 6) Experience influences career planning; 7) Skills affect career planning.